Analisis Nilai-Nilai Pendidikan Agama Islam Pada Tradisi Upah-Upah Masyarakat Desa Kampung Pajak Kab. Labuhanbatu Utara - Situmorang, Hera Yanti; Hasan Matsum; Nasution, Zulkipli (Philosophiamundi, 2024)
The purpose of this study is to find out the Values of Islamic Religious Education in the Tradition of Wages of the Village Community of Kampung Pajak, North Labuhanbatu Regency which is still often carried out by the people of Kampung Pajak. This study uses a descriptive qualitative research method with a phenomenological research approach, where researchers collect data with data collection techniques through interviews, observations and documentation. The results of this study show that the process of implementing the wage tradition carried out by the people of Kampung Pajak Village is by first preparing dishes that will be paid, such as white rice with boiled eggs or white rice with chicken, fish, goats and buffalo and then arranged on plates, tampas or halls. The wages dish is adjusted to what causes a person in wages and the ability of the party who pays the wages. After that, the family gives words of advice to the person who is paid in turn, the first person to convey the words of wages is the father and mother of the person who is paid, then followed by the rest of the family. The tradition of these wages is very good to be implemented because there are Islamic Religious Education values such as the value of faith and morals. The value of faith education contained in the tradition of wages can be seen from the community's belief and compassion towards Allah with the expression of gratitude contained in the advice conveyed, they are grateful for the blessings that Allah gives them, so they carry out the tradition of wages as a form of their gratitude. In addition, there are also worship values such as inviting goodness when conveying the words of wages by the person who pays them. The moral value is also found in the tradition of wages, the value of moral education contained in the tradition of these wages is very good, such as morality to Allah is proven by supplications and requests through prayers, besides that there is a moral value when the community connects the relationship relationship, they gather, meet and strengthen the relationship relationship, this is clearly seen when the tradition of wages takes place.